2018
DOI: 10.1038/s41598-018-28088-4
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Nomogram to Predict Acute Kidney Injury in Patients with Acute Myocardial Infarction Treated Invasively

Abstract: To identify patients who are likely to develop contrast-induced acute kidney injury (CI-AKI) in patients with acute myocardial infarction (AMI), a nomogram was developed in AMI patients. Totally 920 patients with AMI were enrolled in our study. The discrimination and calibration of the model were validated. External validations were also carried out in a cohort of 386 AMI patients. Our results showed in the 920 eligible AMI patients, 114 patients (21.3%) developed CI-AKI in the derivation group (n = 534), whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 21 publications
0
42
0
Order By: Relevance
“…The nomogram is a graphical statistical instrument that incorporates some variables to develop a continuous scoring system, which reflects the individual and precise risk probability. Nomograms are an important part of modern medical decision making, which has been established and validated in extensive medical applications including surgery, cancer, and myocardial infarction [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The nomogram is a graphical statistical instrument that incorporates some variables to develop a continuous scoring system, which reflects the individual and precise risk probability. Nomograms are an important part of modern medical decision making, which has been established and validated in extensive medical applications including surgery, cancer, and myocardial infarction [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The remaining 14 articles were further scrutinized by reading the full text. Four studies were excluded due to an inability to extract a 2 × 2 contingency table [ 30 33 ], and one retrospective study was excluded after discussion between two authors because it used peak NT-proBNP as the cutoff value [ 34 ]. In total, nine studies [ 23 25 , 35 40 ] including 2832 patients fulfilled the inclusion criteria and were ultimately included in this meta-analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Zhou et al. 27 reported that lnBNP is an independent risk factor for contrast-induced acute kidney injury in patients with acute myocardial infarction. Therefore, we suggest that the lnBNP level is a useful marker that is simple and easy to implement in the clinical setting, not only in patients undergoing surgery but also in those with heart disease.…”
Section: Discussionmentioning
confidence: 99%